Evaluation of Spring Loaded Crutch - Uezono, Eiji; Itoh, Yumi; Watanabe, Hideo; Asami, Toyoko; Nishida, Keisuke (Orthopedics & Traumatology, 1998)
Patients with paraplegia often experience slipping of the crutch during swing-through gait on slopes. To solve this problem, we inserted a coil spring into an ordinary axillary crutch and examined its function. We compared the slipping rate and the change in the amount of load on the crutch between the ordinary crutch and spring-loaded crutch. The spring-loaded crutch was found to be superior to the ordinary crutch; it was hard-to-slip and comfortable-to-use. Adjustment of the strength of the coil spring for each patient is considered important.